Detecting, predicting and modifying cardiovascular risk: new and developing strategies. (November 2010) - Shah, Tina; Swerdlow, Daniel
Cardiovascular disease is a leading cause of mortality across Europe and the USA. Epidemiological studies and randomized clinical trials provide strong evidence that coronary disease is largely preventable and can be attributed principally to nine modifiable risk factors. However, a large proportion of coronary events occur in individuals who have intermediate levels of these risk factors, motivating the search for novel markers to improve screening and risk stratification. Work presented at the 78th European Atherosclerosis Society Congress outlined challenges faced in primary prevention as well as novel findings for risk factors. This article focuses on some of these factors, as well as risk prediction and detection, and concludes with the current state of antiatherogenic treatment strategies.